Non-invasive measurement of chick embryo cardiac work - K. Pawlak; J. Niedzióka (Czech Journal of Animal Science, 2004)
This study used a non-invasive method of ballistocardiography to investigate cardiac work of chick embryos. In this method, an eggshell with electric charges on it is one capacitor plate, the other being a receiving antenna of the measuring equipment. Chick embryo cardiac work induces micro-movements of the whole egg, resulting in changes in the distances between the plates and thus in the difference of potentials between the shell and the receiving antenna. This is registered by the measuring equipment. The first single signals of cardiac work were registered on day 7 of incubation. Starting from day 9, the signal was recorded from all embryos. During the study, the heart rate decreased from 248 to 161 beats per minute and signal amplitude was found to steadily increase from 6.3 to 432.7 mV/m. Great disturbances in ballistocardiograms were observed on days preceding embryonic deaths.